The leadership experience in Asia - Lim, Ghee Soon 1961-; Daft, Richard L. (Cengage, 2017)
The Leadership Experience in Asia, Second Edition adopts the leader's perspective in exploring diverse approaches to leading all types of organizations in Asia effectively, with special emphasis on the ways in which leaders in Asia may benefit from using tested concepts and theories that have been proven to be valid in the West. The indigenous element of this Asian edition brings concepts and practices as can be found in Asian organizations to the attention of individual leaders in Asia. Learners will benefit most from this book if they complete all the assessment tools displayed across the various chapters and use the self-profiling results to reflect on their standing against the concepts and theories expounded in the respective chapters. They will learn most effectively if they can relate the contents of the chapters to their past, present, and future or potential places of work.